To what extent should companies integrate UN Sustainable Development Goals into their CSR strategies? A comparative study of UK and Chinese companies in UN Global Compact LEAD initiative - LIAO, MULI (2016)
Purpose – The research aims to find the linkage between UN Sustainable Development Goals (SDGs) and companies’ CSR strategies in order to provide justification to the question that lots of CSR managers are being asked now: Why should companies integrate SDGs into their companies’ CSR strategies? Further research will focus on the approach and method the companies used in the case study to incorporate SDGs in their CSR strategies or activities. The research is being conducted under practical purpose and the author hopes the research findings could provide reference to the CSR practitioners when facing the decision making on this topic.